The impact of education technology on student achievement in School Of Technology Management and Logistics (STML) - Rahmat, Nurul Aimi; Romli, Azizi (Universiti Utara Malaysia, 2020)
Educational Technologies have been considered as a crucial factor in improving the quality of education and enhancing the level of student educational learning performances. The purpose of this study is to describe the impact of STML students using education technology on their achievement with using quantitative analysis. The objective of this study is to investigate the positive and negative effects in using educational technology on student achievement, observe how much students spend their time in using technology and their improvements on the classroom and to investigate the perceived usefulness and perceived ease of use technology among the students and lecturers. By using quantitative research method, the data collected through questionnaire.